History of Uzbek classical children's reading - Jumayeva Dilnoza Tursunpo'lanovna (Zien Journals, 2024)
This article is devoted to the history of children's reading. The article uses examples of classical Uzbek literature
Keywords: Reading; classical literature; children's literature